Pengembangan Sistem Informasi Penanganan Feedback Client Berbasis Web Menggunakan Metode Waterfall - Caesar Yoga Pratama; Marta Ardiyanto; Mira Erlinawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Client feedback management at BIIS Corp still relies on WhatsApp group communication and manual spreadsheet recording, resulting in difficulties in monitoring work progress, inadequate documentation of handling history, and poor coordination between staff and programmers. This study aims to design and develop a web-based client feedback information system to support centralized and structured feedback management. Problem identification was conducted using the PIECES framework, which revealed weaknesses across all six aspects. The system was developed using the Waterfall model within the SDLC framework, with UML-based modeling and functional testing through the Blackbox Testing method. Built using PHP, MySQL, HTML, CSS, and JavaScript, the system accommodates three user roles, namely administrator, staff, and programmer, and is equipped with features including feedback recording, programmer assignment, status updates, completion confirmation, reopen feedback mechanism, real-time notifications, activity log, and performance reporting. Testing across 15 scenarios achieved a 100% success rate. The contribution of this research is the development of a system specifically designed for a software house environment, integrating three user roles into a centralized workflow equipped with a reopen feedback mechanism, real-time notifications, and an activity log to support more effective feedback monitoring and documentation.